PEMBERDAYAAN EKONOMI BERBASIS ZAKAT PRODUKTIF MELALUI BANTUAN ROMBONG UMKM BAZNAS KOTA SURABAYA - Abd Halim AF; Khusnul Fikriyah (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the implementation of an economic empowerment program for mustahik through the utilization of productive zakat in the form of UMKM food-cart assistance implemented by BAZNAS of Surabaya City and to identify factors influencing the success and failure of the program. This research employs a qualitative approach using an ethnographic method. Data were collected through in-depth interviews, field observations, and documentation involving 20 mustahik beneficiaries. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the UMKM food-cart program contributes positively to increased business activity and economic stability among some beneficiaries. However, the level of success varies across recipients. Program success is influenced by internal factors such as prior business experience, entrepreneurial motivation, and basic business management capabilities, as well as external factors including suitability of business type to local needs, strategic business location, and continuity of business mentoring. This study concludes that the effectiveness of productive zakat utilization depends not only on physical assistance but also on the interaction between mustahik capacity and the quality of program implementation.